Social behavior and decision making in bacterial conjugation - Koraimann, Günther; Wagner, Maria A. (Frontiers in Cellular and Infection Microbiology, 2014)
Bacteria frequently acquire novel genes by HGT (horizontal gene transfer). HGT through the process of bacterial conjugation is highly efficient and depends on the presence of conjugative plasmids (CPs) or integrated conjugative elements (ICEs) that provide the necessary genes for DNA transmission. This review focuses on recent advancements in our understanding of ssDNA transfer systems and regulatory networks ensuring timely and spatially controlled DNA transfer (tra) gene expression. As will become obvious by comparing different systems, by default, tra genes are shut off in cells in which conjugative elements are present. Only when conditions are optimal, donor cells – through epigenetic alleviation of negatively acting roadblocks and direct stimulation of DNA transfer genes – become transfer competent. These transfer competent cells have developmentally transformed into specialized cells capable of secreting ssDNA via a T4S (type IV secretion) complex directly into recipient cells. Intriguingly, even under optimal conditions, only a fraction of the population undergoes this transition, a finding that indicates specialization and cooperative, social behavior. Thereby, at the population level, the metabolic burden and other negative consequences of tra gene expression are greatly reduced without compromising the ability to horizontally transfer genes to novel bacterial hosts. This undoubtedly intelligent strategy may explain why conjugative elements – CPs and ICEs – have been successfully kept in and evolved with bacteria to constitute a major driving force of bacterial evolution.